A systemic problem cannot be solved systemically - Maldonado, Carlos Eduardo (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2023)
This paper is a short essay that claims that a systemic problem cannot be rightly understood andeven less solved on the same level, in the same framework or with the same tools that entail thevery same problem. This is a radical variation of Einstein’s idea set out in the context of theCopenhaguen debate according to which a problem cannot be solved if we do not change theconditions in which the problem arose originally. More exactly, a systemic problem cannot betackled and solved with tools, approaches and rods of the very same kind, level, nature offramework that define the problem. To truly tackle and solve any problem, the approach, tools,concepts, models, and the like need have a higher or heavier calibre so to speak than the problem.Otherwise, we do not solve a problem at all. At its best, we displace it. This essay argues that tosolve any systemic problem a complexity endeavour is needed. Reasons for the insufficiency ofsystems science and about the rationale of complexity theory are provided.